EXPLORING THE IMPACT OF INFLUENCER MARKETING STRATEGIES ON SUSTAINABILITY IN THE FASHION INDUSTRY - Fariz Fariz; Tutik Winarsih (Jurnal Manajemen dan Kewirausahaan, 2025)
The rising popularity of social media has compelled businesses to rethink their marketing approaches, focusing on engaging a broader customer base by offering value and facilitating two-way interactions. This shift gave rise to influencer marketing as an innovative brand promotion strategy. When influencers collaborate with brands targeting the appropriate audience, they can enhance brand recognition and add significant value to businesses. This study examines how source credibility factors—such as trustworthiness, attractiveness, and perceived expertise—affect consumer attitudes toward fashion influencers and how these attitudes shape consumers’ intentions to purchase and recommend products. The sample comprises 342 followers of a prominent Indonesian fashion influencer, selected using a simple random sampling method. Hierarchical regression analysis, performed in SPSS, reveals that trustworthiness and perceived expertise significantly impact perceptions of influencers in the fashion industry